Decision-making Behaviour of Traditional Fishermen in Relation to the Adoption of Improved Fishery Technologies - S., Balasubramaniam; M.K., Kandoran; Mohan, Braj (Fishery Technology, 2025)
This study investigates the decision-making behaviour of traditional fishermen in relation to the adoption of improved fishery technologies. Out of eight quantitative variables studied, education and number of crew members had significant and positive correlation with their overall decision making behaviour. ln the multiple regression analysis, the R2 value was 0.2718 and non-significant. Further, the inter-personal sources played a crucial role in the decision-making process of fishermen.